Cerebrospinal fluid biomarkers of demyelination in pediatric population: a single-center study - Hussein M.H Metwally; Ahmed Hassan El-Sheshiny; Ali M Ahmed; Hams A Attalla (Wolters Kluwer Medknow Publications, 2021)
Background Many cerebrospinal fluid (CSF) biomarkers were reported to be associated with demyelinating diseases in adults. Some of these biomarkers are chitinase 3-like 1 (CHI3L1), oligoclonal bands, and neurofilament light chain (NFL). We aimed to investigate the association of CSF CHI3L1 and NFL with demyelination disorders in pediatric patients. Patients and methods All children with age less than 18 years who came to our department with possible demyelinating of neuroinflammatory disorder from the duration between 2009 to 2019 were included in the study. Enzyme-linked immunosorbent assays were used for the analysis of the needed values. Results The data of 97 children were retrieved, and they were categorized as follows: patients with a demyelinating disease (n=17), patients with inflammatory neurological disorders (n=25), patients with systemic inflammatory disorders (n=9), patients with other neurological disorders (n=28), and normal pediatric population (n=18). There was a significant difference between these groups regarding the CSF level of CHI3L1 and NFL, as they were significantly higher in demyelinating disorders rather than other groups. Conclusion The levels of CHI3L1 and NFL in the CSF showed the diagnostic value in demyelinating disorders of pediatric populations and would be effective in distinguishing between different demyelinating disorders.